Double burden of malnutrition and associated factors among mother–child pairs at household level in Bahir Dar City, Northwest Ethiopia: community based cross-sectional study design - Mekonnen, Solomon; Birhanu, Dereje; Menber, Yonatan; Gebreegziabher, Zenebe Abebe; Belay, Mahider Awoke (Frontiers in Nutrition, 2024)
Introduction: The double burden of malnutrition refers to the simultaneous presence of under nutrition and overweight, obesity, or diet-related non-communicable diseases which might occur at population, household, and individual level. The simultaneous presence of overweight/obese mothers with undernourished children in the same household, as well as overweight children with underweight mothers. The prevalence of double-burden malnutrition at the household level has increased significantly in sub-Saharan African countries. However, there is limited knowledge regarding the extent and factors associated with the double burden of malnutrition among mother-child pairs in Ethiopia. Consequently, the objective of this study was to assess the prevalence and determinants of the double burden of malnutrition among mother-child pairs at the household level in Bahir Dar City, Ethiopia. Method: In the year 2021, a community-based cross-sectional study design was employed among 702 mother-child pairs in Bahir Dar city from February 28 to March 23. A multistage sampling technique was used to identify study participants who were interviewed using an interviewer-administered questionnaire.. To determine the strength of association, multivariable logistic regression analysis was performed, and adjusted odds ratios with their respective 95% confidence intervals were computed. Results: The prevalence of the double burden of malnutrition among mother-child pairs was 14.5% (95% CI: 12.8%, 15.7%}. Participants who were in the richest wealth index were 2.72 {AOR=2.72, 95% CI 2.01, 5.63} times more odds of double burden of malnutrition than the poorest. The odds of double burden of malnutrition among children who had high dietary diversity decreased by 63% {AOR=0.37, 95% CI 0.22, 0.61} than low dietary diversity. Food secure households was 1.96 {AOR=1.96, 95% CI 1.13, 3.39} times more likely to have the double burden of malnutrition than food insecure households. The odds of the double burden of malnutrition among mothers who completed college and above decreased by 74% {AOR=0.26 95% CI 0.121, 0.549} than those unable to read and write. Conclusions and Recommendation: The magnitude of the double burden of malnutrition was lower than the Ethiopian Demographic and Health Survey. Wealth index, dietary diversity, food security, and educational status were significantly associated with double burden of malnutrition. T